A Preliminary Study of Formulations of Transfersomes for Improved Transdermal Peptide Delivery - Surini, Silvia; Hutabarat, Rahmi; Bahtiar, Anton; Suryadi, Herman (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Peptide-containing dosage forms are often administered through invasive injection. However, due to their great ultra-mobility, transfersomes offer a promising alternative for non-invasive and non-allergenic transdermal peptide delivery. Therefore, this study aimed to conduct preliminary investigations into the formulations of transfersomes for transdermal peptide delivery. Transfersomes were prepared using the thin-layer hydration method with Tweenâ 80 as an edge activator and Phospholiponâ 90G as vesicle formers. Four formulations: F1, F2, F3, and F4 were optimized with various ratios of the two components, including 90:10, 85:15, 80:20, and 75:25. Particle size, zeta potential, deformability index, polydispersity index (PDI), and vesicle morphology were used to assess transfersomes. As a result, the zeta potential was -37.2 ± 2.19, the deformability index was 1.78 ± 0.03 and the smallest vesicle size (147 ± 1.93), PDI value of 0.105 ± 0.01 and spherical were all found in the optimal formula, F3, with an 80:20 ratio. These results suggest significant potential for the further development of transfersomes using Tweenâ 80 and Phospholiponâ 90G as effective transdermal peptide delivery systems.